Respiratory Distress Syndrome in Neonatal Care Units in Medical City - Hameed, Numan Nafie; Mahmood, Nife Rajab (Journal of the Faculty of Medicine Baghdad, 2008)
Introduction: Neonatal Respiratory distress syndrome (RDS) remains one of the major cause’s neonatal morbidity and mortality despite advances in perinatal care especially in developed countries. Objectives: The aims of this study were to find out me risk factors of mothers and newborns (NB) which increase the incidence, morbidity, and mortality of RDS. Patients & Methods: A prospective descriptive cross-sectional study was conducted on 100 live NR infants born at neonatal care units in Baghdad hospital & private nursing home (medical city complex) / Baghdad in the period from the first of March to the end of June 2006. They were presented with RDS, which was diagnosed clinically and radio-graphically. The study includes preterm and mil term N8 with all birth weights. Results: In tins study, there was an increase in the incidence of RDS in preterm NBs 3.5 times more than in mil term, and 2.0 times more in small for gestational age (SGA) than in appropriate for gestational age (AGA). It was found that the risk of death from RDS with air leak was 11 times more than those without air leak, and from RDS with pneumonia 4.0 times more than those without pneumonia. The risk of death among NB delivered by elective Caesarian section (C/S) was 2.4 times more than those born by emergency C/S. and 5.1 times more in NB of diabetic mothers than those without diabetes. Conclusions: We conclude that prematurity and SGA are risk factors for the development of RDS, and air leak and pneumonia are most important complications that increase the risk of death from RDS. So we recommend a proper and regular antenatal care and. management of high risk pregnancies to avoid premature delivery and SGA, and proper respiratory care of NB to decrease the complications of RDS especially air leak and pneumonia to decrease the risk of death.